Canine Distemper Virus in Autochtonous and Imported Dogs, Southern Italy (2014-2021) - Alfano, Flora; Lanave, Gianvito; Lucibelli, Maria Gabriella; Miletti, Gianluca; D'Alessio, Nicola; Gallo, Amalia; Auriemma, Clementina; Amoroso, Maria Grazia; Lucente, Maria Stella; De Carlo, Esterina; Martella, Vito; Decaro, Nicola; et al. (Animals, 2022)
Simple Summary In the period 2014-2021, the circulation of CDV in dogs of Southern Italy was investigated. In this time span a reduction in the circulation of CDV was observed, with a higher frequency of detection of the pathogen in imported dogs (18.4%) compared to stray (7.4%) and household (3.9%) animals. These results underline the effectiveness of the prophylaxis strategy on autochthonous dogs as well as the importance of continuous surveillance of CDV, especially in imported dogs. This study aims to investigate the presence of canine distemper virus (CDV) infection in 949 autochthonous or illegally imported dogs from Southern Italy, over a period of eight years (2014-2021). CDV RNA was detected in 6.8% (65/949) of the animals tested, with no detection of CDV in dogs sampled in 2020-2021. The frequency of CDV detection was higher in imported dogs (19/103, 18.3%) with respect to stray (27/365, 7.4%) and household dogs (19/481, 3.9%). On sequence and phylogenetic analyses of selected strains, the analyzed viruses belonged to the Arctic clade, which has already been reported in Italy and in Europe. The results of our study may suggest a reduction of CDV circulation in Southern Italy, while at the same time highlighting the need for strict controls on dog importation, in order to prevent the introduction of viruses from endemic countries.